Cross-Religious Collaboration and Leadership in Promoting Social Harmony: Insights from "Kampung Moderasi Beragama” Senduro, Lumajang - Abdus Sair; Umar Sholahudin (Jurnal Sosiologi Agama, 2025)
This article aims to examine the practice of religious inclusivity in the Religious Moderation Village (Kampung Moderasi Beragama or KMB) of Senduro Village, Lumajang Regency. Known for its religious and cultural diversity, Senduro has become an important example of implementing principles of religious moderation in Indonesia. Using a qualitative approach, this study collected data through in-depth interviews with religious leaders, community leaders, and village residents, as well as through participatory observation. The study’s findings reveal that KMB Senduro has successfully fostered a harmonious and inclusive environment through interfaith dialogue, joint activities, local wisdom, and supporting factors, which include inclusive and visionary leadership from the village head, religious figures, and community leaders. These findings further underscore the importance of interfaith cooperation and understanding in maintaining peace and social harmony in a multicultural society like Indonesia, especially in Lumajang Regency.